HLA-B*44 Is Associated with Dengue Severity Caused by DENV-3 in a Brazilian Population - Liciana Xavier Eurico de Alencar; Ulisses de Mendonça Braga-Neto; Eduardo José Moura do Nascimento; Marli Tenório Cordeiro; Ana Maria Silva; Carlos Alexandre Antunes de Brito; Maria da Paz Carvalho da Silva; Laura Helena Vega Gonzales Gil; Silvia Maria Lucena Montenegro; Ernesto Torres de Azevedo Marques (Journal of Tropical Medicine, 2013)
Human leukocyte antigen (HLA) alleles have been correlated with susceptibility or resistance to severe dengue; however, few immunogenetic studies have been performed in Latin American (LA) populations. We have conducted immunogenetic studies of HLA class I and II alleles in a cohort of 187 patients with DENV-3 infection and confirmed clinical diagnosis of either severe dengue, known as dengue hemorrhagic fever (DHF), or the less severe form, dengue fever (DF), in Recife, Pernambuco, Brazil. An association analysis was performed using Fisher’s association test, with odds ratios (ORs) calculated using conditional maximum likelihood estimates. HLA-B*44 (P=0.047, OR = 2.025, 95% CI = 0.97–4.24) was found to be associated with increased susceptibility to DHF in response to DENV-3 infection. In addition, HLA-B*07 (P=0.048, OR = 0.501, one-sided 95% CI = 0–0.99) and HLA-DR*13 (P=0.028, OR = 0.511, one-sided 95% CI = 0–0.91) were found to be associated with resistance to secondary dengue infection by DENV-3. These results suggest that HLA-B*44 supertype alleles and their respective T-cell responses might be involved in susceptibility to severe dengue infections, whereas the HLA-B*07 supertype alleles and DR*13 might be involved in cross-dengue serotype immunity.